2015
DOI: 10.1186/s40064-015-1060-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an enzyme complex on in vitro dry matter digestibility of feed ingredients for pigs

Abstract: Feed ingredients of plant origin are commonly used in swine diets. However, the major components of plant cell walls, non-starch polysaccharides (NSPs), reduce nutrient digestibility. To improve the efficiency of feed utilization, exogenous enzyme products that degrade NSPs have been widely used in commercial animal feeds. Nonetheless, the effects of exogenous enzyme addition to swine diets on nutrient digestibility have not been determined. To this end, in vitro approaches may be used. The objective of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 11 publications
9
19
0
2
Order By: Relevance
“…A greater value of IVTTD of DM compared with the IVID of DM is in consistent with the previous studies (Kong et al, 2015;Navarro et al, 2018). In step 3 of in vitro disappearance procedure, multi-enzyme complex (Viscozyme ® ) containing various NSP-degrading enzymes was used for the digestion of large intestine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A greater value of IVTTD of DM compared with the IVID of DM is in consistent with the previous studies (Kong et al, 2015;Navarro et al, 2018). In step 3 of in vitro disappearance procedure, multi-enzyme complex (Viscozyme ® ) containing various NSP-degrading enzymes was used for the digestion of large intestine.…”
Section: Discussionsupporting
confidence: 90%
“…The IVID and IVTTD of DM in corn (Table 3) were consistent with the previous studies (Kong et al, 2015;Park et al, 2016). However, the IVID of DM in SBMW was slightly greater than the reported value (Navarro et al, 2018) while the IVID of CP and IVTTD of DM in SBMW were close to the reported values (Boisen and Fernández, 1995;Navarro et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…Supplementation of exogenous enzymes in a diet, especially protease as a part of an enzyme mixture, has been widely used to improve the efficiency of nutrient utilization and minimize anti-nutritive effects, and thereby was expected to improve growth performance (Adeola & Cowieson, 2011). In the results of in vitro tests, the addition of enzyme complexes (xylanase, protease and phytase) tended to increase the ileal digestibility of dry matter, even though it depended on test ingredients (Kong et al, 2015). Other studies also showed that enzyme mixtures including protease had a positive impact on nutrient digestibility, bacterial populations in the large intestine, and growth performance of weaned pigs (Yi et al, 2013), faecal nutrient digestibility of growing pigs (Ji et al, 2008), and the performance of growing pigs without improving apparent total tract digestibility (Jo et al, 2012).…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, the method of maximizing the potential available N in the existing diet is very significant. The use of exogenous protein enzymes in swine diets is a common strategy to ameliorate anti-nutritive effects of SBM and to improve the efficiency of N utilization (Kong et al, 2015). …”
Section: Discussionmentioning
confidence: 99%